Study of the reliability of the lateral photograPhs of the face in determining the structural disparties in Class II division 1 Patients - حسن, عبد الكريم توفيق; تيزيني, محمد عبد الله; كوسه, بشار محمد (Latakia University Journal -Medical Sciences Series, 2021)
Research background and aim: Lateral cephalometric radiographs are the most reliable method for detecting and determining skeletal and dental alveolar disorders. This type of radiograph is misconstrued as the dose that the patient may receive. Hence, many studies have sought to try to replace this technique with a less dangerous one, using lateral facial profile photographs. Materials and Methods: A sample of (31) patients who attended the orthodontic department at the Faculty of Dentistry at Tishreen University and who corresponded with Inclusion criteria (Skeletal ClassII ANB > 4) were collected. The radiographs were traced using the WEBCEPH program, and the optical images were drawn using the MICRODICOM program. Results: Pearson's correlation coefficient was performed between measurements (ANB, FH-NPog, AN Pog) obtained from radiographs and measurements (A`N`B`, FH N`Pog`, A`N`Pog`) obtained from optical images respectively. The results showed that there were statistically significant differences between the measurements (ANB, AN Pog) and the measurements (A`N`B`, A`N`Pog`) respectively, while there were no statistically significant differences between the measurements of (FH-NPog) and (FH-N`Pog`) at the significance level of P < 0.05. Conclusion: It is not possible to rely on the lateral facial profile photographs in determining the skeletal classII cases. Recommendations: Reliance on the lateral cephalometric radiograph as a basic determinant of structural disparities in the anteroposterior directions.